EKSISTENSI PONDOK PESANTREN SALAFI - Ditha Prasanti (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2017)
This paper discusses Pesantren Miftahul Huda and factors that cause this salafi pesantren chose to maintain its salafiyyah in this modern era. This research used qualitative approach with a method of case study. The result of this research shows that the factors that make the salafi pesantren Miftahul Huda exists in this modern era are: first, the belief in the teachings of Islam spread by Walisongo (Nine Saints) that the first Islamic education in the land of Java is a salafi pesantren; Second, the mandate of the ancestors of who had pioneered the pesantren the salafi pesantren must exist until the end of time; Thirdly, Pesantren Miftahul Huda as salafi pesantren which was first established in Tasikmalaya in 1967 has a good management in establishing the strategy of developing salafi pesantren.